Osteoclast Signal Transduction During Bone Metastasis Formation - Győri, Dávid S.; Mócsai, Attila (Frontiers in Cell and Developmental Biology, 2020)
Osteoclasts are myeloid lineage-derived bone-resorbing cells of hematopoietic origin. They develop from macrophage-like precursors through a complex regulation process where the differentiation of preosteoclasts is followed by intercellular fusion to generate large multinucleated cells. Under physiological conditions, osteoclastogenesis is primarily directed by interactions between CSF-1R and macrophage colony-stimulating factor (M-CSF, CSF-1), receptor activator of nuclear factor NF-κB (RANK) and RANK ligand (RANKL), as well as adhesion receptors (e.g. integrins) and their ligands. Osteoclasts play a central role in physiological and pathological bone resorption and are also required for excessive bone loss during osteoporosis, inflammatory bone and joint diseases (such as rheumatoid arthritis) and tumor cell-induced osteolysis. Due to the major role of osteoclasts in these diseases the better understanding of their intracellular signaling pathways can lead to the identification of potential novel therapeutic targets. Non-receptor tyrosine kinases and lipid kinases play major roles in osteoclasts and small-molecule kinase inhibitors are emerging new therapeutics in diseases with pathological bone loss. During the last few years, we and others have shown that certain lipid (such as phosphoinositide 3-kinases PI3Kβ and PI3Kδ) and tyrosine (Src‐family and Syk) kinases play a critical role in osteoclast development and function in humans and mice. Some of these signaling pathways shows similarity to immunoreceptor-like receptor signaling and involves various other enzymes (e.g. PLCγ2) and adapter proteins (such as the ITAM‐containing adapters DAP12 and the Fc-receptor γ-chain). Here, we review recently identified osteoclast signaling pathways and their role in osteoclast development and function as well as pathological bone loss associated with osteolytic tumors of the bone. A better understanding of osteoclast signaling may facilitate the design of novel and more efficient therapies for pathological bone resorption and osteolytic skeletal metastasis formation.